Coordination Analysis of Urban Water-Energy-Food Nexus Based on Policy Regulation - Gao, Chengkang; Yu, Meng; Zhang, Shuaibing; Zhu, Sulong; Na, Hongming; Li, Xiaojun (Journal of Environmental Accounting and Management, 2026)
As the rapid population and socio-economic growth together with the shortage of resources such as water, energy, and food. The shortage of resources made serious challenges for the management department of water, energy, and food in cities. A metabolic network of water, energy and food in cities was established in this study according to the material flow analysis method. The metabolic characteristics of water, energy and food in the socio-economic system of Guangzhou from 2013 to 2017 were quantitatively analyzed, and evaluation indicators were established for the development status of the city. A kinetic model of the Water-Energy-Food system in Guangzhou was constructed to simulate and predict the future development trend of resource demand in Guangzhou with different policy regulations. It was found that the total water resources of Guangzhou decreased from 6.84×10^9 m3 to 6.53×10^9 m3 from 2013-2017. The total energy input increased from 5.38×10^7 tce to 6.23×10^7 tce, an increase of about 15.9%, and the food (N) input increased by 1.06×10^5 t from 1.06×10^5 t, an increase of about 44.4%. It further indicates that the sustainable development potential of the WEF system in Guangzhou was strong. By increasing the proportion of recycled water reuse, promoting waste separation, improving the resource utilization rate of waste, and implementing strict electricity consumption policies, water demand of 51.25×10^8 m3, the energy demand of 7.27×10^7 tce, the total food (N) demand of 6.85×10^4 t, and the total waste (N) entering the environment of 1.09×10^5 t in 2030 in Guangzhou. Hence, 25% increase in the utilization rate of recycled water, 2% increase in electricity price, 50% increase in the utilization rate of waste recycling are selected as sustainable water, energy and food resources management policies.